KOORDINASI DAN SUPERVISI KOMISI PEMBERANTASAN KORUPSI DALAM MENCEGAH DAN MEMBERANTAS TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN KORUPSI - Indra, Maxasai; ', Syahrul; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Corruption in Indonesia is widespread in society. In law enforcement, corruption, of the Corruption Eradication Commission can not do it alone, given the vast area of Indonesia. Corruption Eradication Commission should cooperate with other law enforcement agencies. Undag Act No. 30 of 2002 explained that the Corruption Eradication Commission may conduct coordination and supervision against Corruption, and act as Coordinator of the Institute. Coordination and supervision is done during this time to experience the tension between the phases of the Anti-Corruption Commission with the Indonesian National Police, for example, is the case of the SIM Simulator. The purpose of writing this thesis: first, to determine the coordination and supervision arrangements in preventing and combating corruption in Indonesia. Secondly, To know the concept of coordination and supervision ideally in preventing and combating corruption in Indonesia. From the research there are two main things that can be inferred. First, the function of coordination and supervision remains a secondary function of the Corruption Eradication Commission, in addition to the MOU of 2012 on Optimization of Anti-Corruption Coordination and Supervision weaken the authority possessed by the Corruption Eradication Commission. In practice there are sectoral ego, it arises as a result of an investigation into corruption can be done by several investigators agencies. Additionally Limitations of Human Resources is also a problem of weak coordination and supervision of the Corruption Eradication Commission. Second, to improve the coordination and supervision of one of the ways you can do is to establish the Integrated Anti-Corruption Coordination Center (SKPKT), so that the cooperation between the Corruption Eradication Commission, the Police and the Attorney General can be done with the same institutional standards.Keywords : Coordination - Supervision- Corruption Eradication Commission – Prevention - Corruption